FORMULASI EKSTRAK ETANOL DAUN MALAKA (Phylanthus emblica) DALAM SEDIAAN MASKER GEL PEEL-OFF - Agustina Bayo Inggirik Mogan; Ni Luh Arpiwi; Ni Nyoman Wirasiti (Program Studi Biologi Universitas Udayana, 2024)
The use of facial masks is useful for softening the skin, nourishing and opening clogged pores, helping prevent premature aging, and reducing the appearance of fine lines and wrinkles. Plants that can be used as active ingredients are malaka, or amla (Phyllanthus emblica L.), a natural source of antioxidants. This study aims to determine the content of phytochemical compounds in the ethanol extract of Malaka leaves, to analyze the antioxidant activity and IC50 of the ethanol extract of Malaka leaves, to determine the quality of the peel-off gel mask with the addition of the concentration of the ethanol extract of Malaka leaves and to find out which formulation is preferred by Probandus. The research design used a completely randomized design (CRD) using Malaka leaf extract with concentrations F0(0%), F1(1%), F2(2%) and F3(3%). The phytochemical content test of Malaka leaf extract showed the presence of flavonoids (0.467%) and tannins (10.97%). The antioxidant activity of the ethanol extract of Malaka leaves was 1.3314% and IC50 was 30 ppm. The organoleptic test results for all preparations did not change during 5 weeks of storage, pH 5.37-5.54, the viscosity of the mask preparation was 50000-126000 cps, the peel-off gel mask preparation was homogeneous and did not . Statistical analysis of the